POST-HARVEST FUNGAL PATHOGENS OF ONION BULBS SOLD IN MARKETS IN JOS METROPOLIS, NIGERIA - Telzin, Dinchi P.; Damdam, Nanven A.; Iro, Ibrahim I.; Obidola, Shakirdeen M.; Dogun, Ojochogu; Habib, Lawal I. (FUDMA Journal of Sciences, 2026)
Onions (Allium cepa L.) are an important vegetable crop in Nigeria, contributing substantially to food security and economic sustainability. However, post-harvest fungal spoilage remains a major constraint, resulting in considerable losses. This study investigated the fungal pathogens associated with onion bulb deterioration in markets within the Jos metropolis, Plateau State, Nigeria. A total of 180 onion bulbs were sampled from four major markets, including 120 visibly spoiled bulbs collected directly from vendors and cultured on Potato Dextrose Agar. In addition, 120 apparently healthy bulbs from the same markets were monitored for fungal infection and spoilage progression over a three-week period, while 40 bulbs (10 per market) served as controls. Data were analyzed using descriptive statistics, including frequencies and percentages. Four fungal species were isolated and identified: Aspergillus niger, Cladosporium cladosporioides, Fusarium oxysporum, and Penicillium citrinium. Aspergillus niger was the predominant pathogen, recording the highest frequency of occurrence, spoilage rate (99.9%), disease incidence, and associated weight loss. This was followed by C. cladosporioides (40%), F. oxysporum (33.33%), and P. citrinium (19.97%). The results confirm that these fungi are key contributors to post-harvest onion bulb decay in the study area. Some of the isolated fungi are also of public health concern, while others accelerate product deterioration. Effective control of contamination during harvesting, handling, storage, and distribution is therefore essential to reduce spoilage, minimize economic losses, and lower the risk of food-borne illnesses associated with raw onion consumption.
Keywords: Isolation; Fungi; Spoilage; Post-harvest; Allium cepa (Onion bulb)